Fine sediment particle microscopic characteristics, bioavailable phosphorus and environmental effects in the world largest reservoir. (October 2020) - Wang, Xiaoxiao; Zhou, Jun; Wu, Yanhong; Bol, Roland; Wu, Yong; Sun, Hongyang; Bing, Haijian
Abstract: The transport and retention of sediments in fine grain sizes plays an important role in the cycles of phosphorus (P), and is closely related to the extent and potential for eutrophication in water reservoirs. In order to highlight the environmental indications for the transport of fine sediment particles and the associated bioavailable phosphorus (Bio-P) in the world largest reservoir, the Three Gorges Reservoir (TGR), the suspended and bed sediments were collected at 13 sections in 2016. The sediment physicochemical properties, micromorphology of sediment particles, distribution of elements on particle surface, P adsorption parameters, and P fractions in different grain sized sediments were analyzed. The results showed that the fine sediment particles had a strong P adsorption ability due to their micromorphology, mineral compositions, and the high contents of Fe/Al/Mn (hydr)oxides, which contributed a higher concentration of Bio-P in <16 μm sediment particles. The adsorption of P on the sediment particles occurred longitudinally along the TGR, and the fine sediment particles (<16 μm) dominated the transport and distribution of Bio-P in the TGR sediments. The reduced inflow and retention of fine sediment particles, caused by the construction of cascade reservoirs along the Jinsha River (upper reach of the Yangtze River), has resulted in the decrease in the retention of Bio-P in the TGR. Therefore, we conclude that the continuously decrease of inflow and retention of the fine sediment particles in the TGR, and with it a reduced sediment P buffer capacity, may enhance algal blooms occurrence also in view of the increased P discharge from the overall TGR catchment. The study results can contribute to improved management guidance on fine sediment particles and associated phosphorus for the operation and environmental protection of other large reservoirs in the world. Graphical abstract: Image 1 Highlights: Microscopic characteristics of fine sediments were highlighted in the TGR. Fine sediment particles (<16 μm) dominated the fate of Bio-P in the TGR. Continuously decrease in inflow of fine particles reduced P buffer capacity. Occurrence of eutrophication may be enhanced due to reduced sediment inflow.